Performance of pervious concrete containing combined recycled aggregates (2018)
This study evaluates the influence of incorporating two different types of recycled aggregates (RA) from construction and demolition waste (CDW), brick ceramic aggregate (RA1) and crushed concrete aggregate (RA2), from the city of Bogotá, on the performance of pervious concrete under compression and flexural strength. The substitution of RA in the production of pervious concrete is outlined, taking into account five substitution levels. For the pervious concrete mixes, aggregates of sizes retained in a sieve of 1/2” and 3/8” were used. The pervious concrete mixes were submitted, 28 days later, to density tests, void content, compression and flexural strength and permeability. Such pervious concrete with RA reaches compression and flexural strength of up to 5,79 MPa and 2,14 MPa, respectively, which are within the allowed range by the ACI, reaching a permeability of 24,79 mm/s, value that is superior to the common characteristics of pervious concrete